A subject specialist-centric model for library resources management in academic libraries. Issue 4 (4th July 2016) - Chen, Mingyue; Makani, Joyline; Bliemel, Michael
Abstract : Purpose: The purpose of this study is to analyze factors affecting decision-making on libraries' electronic resources management under the situation of tight budgets in Canadian research universities. Design/methodology/approach: Interview was adopted to investigate library resources management leaders' opinions from English-speaking university members of the Group of Canadian Research University Libraries. Findings: A comprehensive model is developed for library resources' management. Subject specialists are the key of the model integrating marketing roles and evaluation roles. Research limitations/implications: The main limitations of this study are the small sample size of interview candidates, which may have application limitations on other types of libraries and universities in different areas. Practical implications: This study generates a comprehensive model based on past research, contributing to future library decision-making practices. Originality/value: It develops a subject specialist-centric model of library resources' value assessment and brings the element of culture into future studies of academic library.